Realizing the Abidjan Principles on the Right to Education Human Rights, Public Education, and the Role of Private Actors in Education - Adamson, Frank; Aubry, Sylvain; de Koning, Mireille; Dorsi, Delphine (NORRAG Series on International Education and Development, 2021)
This insightful book analyses the process of the first adoption of guiding human rights principles for education, the Abidjan Principles. It explains the development of the Abidjan Principles, including their articulation of the right to education, the state obligation to provide quality public education, and the role of private actors in education.